Piscirickettsia salmonis-Triggered Extracellular Traps Formation as an Innate Immune Response of Atlantic Salmon-Derived Polymorphonuclear Neutrophils - Alarcón, Pablo; Espinosa, Gabriel; Millán, Catalina; Saravia, Julia; Quinteros, Vania; Enriquez, Ricardo; Henríquez, Claudio; Vargas-Chacoff, Luis; Burgos, Rafael A; Taubert, Anja; Hermosilla, Carlos; Morera-Galleguillos, Francisco Javier (Biology, 2021)
Simple Summary: Within innate immunity, polymorphonuclear neutrophils (PMN) are the most abundant leukocyte population. Alongside PMN, monocytes, eosinophils, and basophils are also known to exist. All of them can release extracellular traps (ETs), a comp This research was funded by the following Grants: FONDECYT REGULAR 1180957 (to F.J.M. and L.V.C.); DID-UACH S-2016-22 (to F.J.M. and L.V.C.), and FONDAP IDEAL 15150003 (to L.V.C.). Julia Saravia is funded by Comision Nacional de Investigacion Cientifica y FONDECYT REGULAR Proyectos de Investigación FONDECYT REGULAR [1180957]; DID-UACH [S-2016-22]; FONDAP IDEAL [15150003]; Comision Nacional de Investigacion Cientifica y Tecnologica; Agencia Nacional de Investigacion y Desarrollo (ANID) [21170636] wos 3 10